Muslim Consumers’ Behaviour Towards Halal Nutraceutical Products In Malaysia - Siti Nurunnajwa, S.; Elistina, A.B.; Syuhaily, O.; Nuradli Ridzwan Shah, M.D. (Rynnye Lyan Resources, 2024)
Food Research, Volume 8 Issue 3 Page (402–407)